Experimental study on the influence of cutting distance on the rock-breaking features of pick-shaped cutter - LIU Bin; LI Xuefeng (Gong-kuang zidonghua, 2023)
The pick-shaped cutter is the most widely used cutter type in mining machinery such as roadheader and coal mining machine. In the actual cutting process, the pick-shaped cutter mainly works under the multi-tooth coupling cutting condition. The cutting distance is an important parameter under this working condition. At present, research on the influence of cutting spacing on the rock-breaking process has not considered the weakening effect of interference cutting. A calculation method for cutting force during multi-tooth coupling cutting is proposed to solve the above problem. Full-size single-tooth cutting tests are carried out on limestone, red sandstone and two simulated rock samples, comparing and analyzing the rock-breaking processes of free cutting and interference cutting. The experiment collects cutting force data and conducts noise reduction processing and collects cutting debris to analyze the impact law of cutting spacing on cutting load, cutting debris coarseness, cutting energy consumption, and cutting grooves. The experimental results show the following points. ① The cutting force of the cutter increases with the increase of cutting distance and gradually approaches the free cutting state. Moreover, there is a good linear relationship between the cutting force ratio under interference cutting and free cutting conditions and the cutting distance/cutting depth. The correlation coefficients are greater than 0.95. The cutting load of the cutter under interference cutting conditions can be estimated using the free cutting load. The cutting force estimation equation under interference cutting conditions based on the existing peak cutting force model is obtained. ② The coarseness index (CI) and specific energy (SE) are used respectively to evaluate the particle size distribution and cutting energy consumption of the cutting experiment. As the cutting distance increases, CI shows a trend of first increasing and then decreasing. SE shows a trend of first decreasing and then increasing. ③ When the cutting distance is small, the interference between the cutting grooves is significant, the residual rock ridges between the cutting grooves are small, and the cutting load is small. However, due to the interference between the cutting grooves, more small debris is generated. It consumes more energy and increases energy consumption. As the cutting distance increases, the residual rock ridge increases, and the cutting force increases. However, due to the weakening effect of existing cutting grooves on the rock and less interference between cutting grooves, the proportion of large debris formed increases, and the cutting energy consumption decreases. As the cutting distance further increases, there is no interference between the cutting grooves. The weakening effect of the existing cutting grooves on the rock decreases. The cutting force increases, the coarseness decreases, and the cutting energy consumption increases. The cutting state gradually approaches free cutting.